A model to unravel the beneficial contributions of trace Cu in wrought Al–Mg alloys. (15th April 2021) - Medrano, S.; Zhao, H.; Gault, B.; De Geuser, F.; Sinclair, C.W.
Graphical abstract: Abstract: The softening and strengthening contributions in pre-deformed and aged Al–Mg–Cu alloys containing 3 wt.%Mg and 0.5 wt.%Cu are evaluated by a combination of microscopy, mechanical testing and modelling. A refined phenomenological model for the work hardening response, accounting for the separate effects of recovery and precipitation, is shown to be suitable for an unambiguous determination of the precipitation hardening contribution in these alloys. Significantly, it is found that the mechanical response of these alloys is not strongly impacted by Cu content (in the low Cu content regime), pre-deformation level or aging temperature meaning that the alloys are robust with respect to variations in composition. This is interesting from the perspective of alloy design concepts based on 'recycling friendly' compositions in applications that include paint-baking.